Sperm impairments in adult vesper mice (Calomys laucha) caused by in utero exposure to bisphenol A. (23rd October 2013) - Vilela, J.; Hartmann, A.; Silva, E. F.; Cardoso, T.; Corcini, C. D.; Varela‐Junior, A. S.; Martinez, P. E.; Colares, E. P.
Summary This study aimed to evaluate the effects of in utero administration of bisphenol A (BPA) on semen parameters of vesper mice. Sixty female Calomys laucha were divided into six groups and received by gavage during gestation the following substances: Water (negative control), Olive Oil (vehicle control), Diethylstilbestrol (DES – positive control – 6.5 μg kg−1 bw) and BPA (40, 80 and 200 μg kg−1 bw). Male offspring were euthanised at 70 days of age, and sperm parameters were analysed. BPA reduced normal sperm morphology (water = 96.1 ± 0.65; BPA200 = 96.8 ± 2.3%), sperm membrane integrity (water = 88.8 ± 1, 65; BPA200 = 70.6 ± 4, 15%), sperm motility (water = 87.5 ± 1.71; BPA200 = 51.3 ±9.9%) and in vitro penetration rates (water = 55.0 ± 7.14; BPA200 = 7.47 ±2.96%), but it did not affect body weight, anogenital distance, sperm DNA integrity and acrosome integrity. In conclusion, in utero exposure to BPA caused a reduction in sperm parameters of adult C. laucha. Natural mating studies should be conducted to verify the effects of BPA on fertility of the animals.